Taxing Multinationals in Europe - Crivelli, Ernesto; International Monetary Fund. Development Committee (Washington, D.C International Monetary Fund (IMF), 2021)
This paper aims to contribute to the European policy debate on corporate income tax reform in three ways. First, it takes a step back to review the performance of the CIT in Europe over the past several decades and the important role played by MNEs in European economies. Second, it analyses corporate tax spillovers in Europe with a focus on the channels and magnitudes of both profit shifting and CIT competition. Third, the paper examines the progress made in European CIT coordination and discusses reforms to strengthen the harmonization of corporate tax policies, in order to effectively reduce both tax competition and profit shifting. (IMF page)
Acknowledgments -- Executive Summary -- 1. Introduction -- 2. The Corporate Income Tax and the Role of Multinational Enterprises in Europe -- 3. Corporate Tax Spillovers in Europe -- 4. European Tax Coordination -- 5. Conclusions -- References
on title page: European and Fiscal Affairs Departments
Includes bibliographical references (pages 43-49)
Keywords: Business enterprises; BUSINESS ENTERPRISES; CORPORATIONS; TAXATION; EUROPE